How to Assess Reverse Logistics of e-Waste Considering a Multicriteria Perspective? A Model Proposition - Patricia Guarnieri; Lucio Camara e Silva; Bárbara de Oliveira Vieira (Logistics)
As e-waste exponentially increases on a global scale, some legislation and plans to implement reverse logistics have arisen in some countries. While reverse logistics is already well consolidated in developed countries, it is still in a state of infancy in developing countries. In this article, we propose a theoretical model to assess reverse logistics, based on a multicriteria decision aid perspective. This was done while considering a context in which the implementation of the reverse logistics of e-waste is at the beginning. To show the main characteristics of the literature and obtain the model’s inputs, we conducted a systematic literature review to help us understand the main criteria and methods used for this purpose. Then, we illustrated the use of the proposed model with a numerical example. This paper contributes to the current body of research, and aims to assist practitioners within the field of reverse logistics by systematizing the knowledge related to this issue, and offering a model that can guide the decision-making. This model differentiates from others already published because it uses the probabilistic composition of preferences (PCP) method, which does not require the assignment of weights. The model can also be used while considering the preferences of several decision-makers, therefore covering several points of view and providing a more holistic view of the decision problem.